Research on the industrialization development path of Taijiquan industrialization in Henan Province under the background of Healthy China - Zhou, Yangyang (The Journal of the International Society of Chinese Health Practices, 2021)
Objective: Taking the development path of Taijiquan in Henan Province, explore the path of Taijiquan industrialization, develop the development of Taijiquan, and strengthen the research on the development of Taijiquan. For the development of health industry, the development of Taijiquan, promote the development of health service industry of Henan Province, and then promote the economic growth of Henan Province; for the masses, is conducive to the development of fitness projects, enhance the physical quality of the people, enhance the health preservation. The concept of meaning, to build a harmonious society. Methods: 2. 1 Literature method, by consulting the core journals, doctoral papers and works of the Chinese website and the library, we understand the relevant content of Taijiquan industrialization and the function of Taijiquan fitness and health, and provided rich information for this research. 2. 2 Investigation method, through the expert interview method and questionnaire investigation method, systematically investigated the resources and development advantages of Tai Chi in Henan Province, and integrated the Taiji resources. 2. 3 Logical analysis method, which will systematically organize the data, logically analyze the relationship of Taijiquan industry development in Henan Province, and find the industrial development of Taijiquan industry advantages, to formulate the industrialization development strategy of Henan Province Taijiquan. Results: (1) The promulgation of the policy is a strong support for the industrialization development of Taijiquan in Henan Province. The Outline points out that the focus on popularizing healthy life, construction of healthy environment and development of health industry is to improve the health level and fairness. The development of Taijiquan industry can promote the prosperity and development of the health industry. (2) Taijiquan has been listed as the representative list of the world intangible cultural heritage, which is a good opportunity for the Taiji group industry to enter the world. The birthplace of (3) Taijiquan is in Henan Province, which has a rich talent resources of Taijiquan. (4) Taijiquan and health care are close to the inseparable connection, practicing Taijiquan is the best way to keep health. 3. 2 According to the investigation of the industrialization development of Taijiquan in Henan Province, (1) Taijiquan industrialization development lacks overall planning. Currently, there are many Taijiquan training institutions in Henan Province, but the industrialization development of Taijiquan lacks planning. (2) The publicity of Taijiquan is not enough to be effectively combined with the online media. The development of Internet technology and the 5G era has attracted the attention of the public, and the simple publicity of Taijiquan has no longer been able to attract the attention of the public. (3) The Taijiquan industry in Henan Province has just started, and its slow development has not established corresponding links with other industries. Guide The Taijiquan industry chain is relatively short. The (4) government does not pay enough attention to and support the industrialization development of Taijiquan. 3. 3 Taijiquan industrialization development path of Taijiquan (1), by 2030, began to take scale, promote the employment problem of Henan Province; by 2035, Taijiquan industrialization will mature and promote the economic development of Henan Province. (2) industrialization development mode, the development mode of combining online and offline with home and abroad, will publicize and promote it from Taijiquan health preservation, Taijiquan culture, Taijiquan tourism, Taijiquan competition and other aspects. (3) Principles of industrialization development, adhere to the can The principle of sustainable, high-quality and international development leads to the development of the sports industry in Henan Province towards internationalization. (4) Industrialization talent training, industrialization development of Taijiquan needs to cultivate Taiji health and rehabilitation talents; international exchange talents; combined with Internet technology, etc. (1) The Henan Provincial Government should see the development prospect of Taijiquan and provide strong support for the integrated development of Taijiquan and tourism. (2) Establish a market access mechanism for the industrialization and development of Taijiquan, so that the market development of Taijiquan has rules to follow. (3 ) The education circle should conduct in-depth research on the industrialization of Taijiquan, strengthen cooperation with multiple disciplines, and cultivate diversified reserve talents of Taijiquan. (4) All enterprises should establish a communication mechanism with the development of Taijiquan, strengthen cooperation with Taijiquan, increase investment, develop characteristic industries in Henan Province, promote the industrialization of Taijiquan in Henan Province, and help the construction of a healthy China. Conclusion: Study the industrialization of Taijiquan in healthy China. Henan Province has strong advantages to promote the industrialization development of Taijiquan, but faces many problems on its industrialization development road, such as the insufficient publicity of Taijiquan industrialization, the less research of Taijiquan industrialization, the insufficient attention of the government and so on. In order to promote the industrialization of Taijiquan, the government attaches great importance to, provide policy support and establish a market access mechanism for the industrialization of Taijiquan, so that the industrialization of Taijiquan has rules to follow. The Ministry of Education strengthens the training of diversified reserve talents of Taijiquan, and enterprises increase the development of Taijiquan Investment efforts to promote the development of the industrialization of Taijiquan in Henan Province, and help the construction of a healthy China.